Pre-switching bifurcation of a slender jet - Audier, Pierre Marcel Roger (2016)
In this work, we study the near-field of the jet flow exiting a slot-model with aspect ratio 7.5:1. The core of the slender jet separates into two streams which subsequently merge recomposing a single core jet. Axis switching occurs downstream following self-similarity rules. In order to unveil the 3D dynamics of this pre-switching bifurcation, stereo-PIV (Particle Image Velocimetry) measurements are performed and a phase-locking technique is implemented using surface dielectric barrier discharge plasma actuators. The device forces the flow with low-amplitude localized disturbances to produce a lock-on phenomenon. The symmetric modes of the Crow instability, developing between the counter-rotating vortex tubes formed at the slot exit, are found to account for the bifurcation process.